Physical oceanography during RV SENCKENBERG cruise SE202203-2 - Michelle Albinus; Anna-Lena Geßner; Helge-Ansgar Giebel; Jens Meyerjürgens; Jochen Wollschläger; Thomas Henry Badewien (PANGAEA, 2025)
Data presented here were collected during the cruise SE202203-2 with RV Senckenberg from Neuharlingersiel, Germany to Neuharlingersiel, Germany (March, 28th, 2022 to March 30th, 2022). In total, 33 vertical deep CTD-hauls were conducted. The CTD system used was a Sea-Bird Electronics Inc. SBE 19plus V2 probe (SN 7245). The CTD was attached to a SBE 55 Carousel Water Sampler (SN 5571979-0100) containing 6 4-liter Ocean Test Equipment Inc. bottles. The system was equipped with additonally an altimeter (Benthos, SN 4711), and a double chlorophyll fluorometer (SCUFA Turner, SN 0773). The sensors were pre-calibrated by the manufacturers. Data were recorded with the Seasave V 7.26.7.107 software and processed using the SeaBird SBE Data Processing. Data were converted, filtered, loop edited and bin averaged (size 0.25 m) and also visually checked. The ship position was derived from a trimble DGPS-system linked to the CTD data. The time zone is given in UTC. For more details on post-processing see the CTD processing report attached. Raw data on request.